Simultaneous electrochemical detection of uric acid, dopamine and ascorbic acid using poly (3,4-ethylenedioxythiophene)/reduced graphene oxide/manganese dioxide - Tukimin, Nurulkhalilah (2018)
The coexistence of uric acid (UA), ascorbic acid (AA) and dopamine (DA) in human body system is difficult to be measured due to their close oxidation potentials. The abnormal level of these analytes in human body would lead to various diseases. In order to solve this problems, poly(3,4-ethylenedioxythiophene)/reduced graphene oxide electrode (PrGO) and manganese dioxide deposited on PrGO (PrGO/MnO2) composites were prepared using cyclic voltammetry for UA detection in the presence of AA and simultaneous detection of UA, AA and DA, respectively. The PrGO and PrGO/MnO2 composites showed an improved electrocatalytic activity towards the oxidation of analytes in pH 6.0 (0.1 M PBS). The PrGO/MnO2 electrode was able to detect UA, AA and DA simultaneously while, PrGO composite was only able to detect UA in the presence of AA, indicating PrGO/MnO2 composite has better catalytic activity than PrGO composite which lead to the current increased and good peak potential separation (ΔEp) of each analyte. The limit of detection and sensitivity of PrGO for the detection of UA are 0.19 μM (S/N = 3) and 0.01 μA/μM, respectively in the range of 1-300 μM. The PrGO/MnO2 electrode has detection limits towards UA, AA and DA with the values of 0.05, 1.00 and 0.02 μM with a linear response of 1-800, 0.03-45 and 0.3-80 μM, respectively. The ΔEp values of AA-DA, AA-UA and DA-UA were 166, 312 and 146 mV, respectively. Both sensors also showed an excellent reproducibility and repeatability towards the analytes.